New picture archiving and communications system plus new facility equals critical path planning challenge...Proccedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston TX, May 6-9, 1999 - Brye PE; Loharikar R; Duda E (Journal of Digital Imaging)
The architectural design and construction of a new imaging department is one of the most complex challenges in healthcare architecture. When a client also plans a simultaneous change in basic operating system technology from film-based to filmless imaging, the challenge for both hospital management and the facility/technology design team is even more complicated. A purposeful planning process plus a carefully composed team of internal and external experts are the two essentials for success in executing this difficult conversion of both facility and technology. Copyright (c) 1999 by W.B. Saunders Company